Behaviours of phoretic mites (Acari) associated with Ips pini and Ips grandicollis (Coleoptera: Curculionidae) during host‐tree colonization. (21st December 2015) - Pfammatter, Jesse A.; Malas, Kareem M.; Raffa, Kenneth F.
Abstract : Studies on interactions between bark beetles and phoretic mites have focused largely on dispersal life stages. However, many of these interactions occur within trees, where beetles and mites develop. Within‐tree interactions are potentially important to beetle and mite reproduction, as well as beetle–mite phoretic pairings. We performed experiments aiming to characterize the behaviours of mites associated with Ips pini (Say) and Ips grandicollis (Eichoff) during nondispersal life stages. Mites are highly specific in the location on which they attach to beetles. Detachment from beetles is elicited by cues associated with both beetle vectors and tree hosts. Beetle condition can trigger rapid mite departure and Iponemus confusus Lindquist detach more rapidly from beetles colonizing tissue amended with the host tree secondary compound α‐pinene than in un‐amended tissue. Within‐plant movement by detached mites is elicited by host plant volatiles. In olfactometer assays, Dendrolaelaps quadrisetus (Berlese) preferred volatiles from beetle‐infested phloem over fresh phloem and blank controls. Within host plant tissue, fungal symbionts of beetles provide a resource for mites. Histiogaster arborsignis Berlese fed and reproduced more successfully on Pinus resinosa (Ait) phloem inoculated with the symbiotic fungus Ophiostoma ips (Rumbold) than on phloem with the opportunistic fungus Aspergillus fumigatus or blank controls.